KAJIAN KEBERHASILAN PENGGUNAAN SISTEM INFORMASI ACCURATE DENGAN MENGGUNAKAN MODEL KESUKSESAN SISTEM INFORMASI DELON DAN MCLEAN - Jamal Maulana Hudin; Dwiza Riana (Jurnal Sistem Informasi, 2016)
Accurate accounting information system is one of accounting information systems used in the sixcompanies in the city of Sukabumi. DeLone and McLean information system success model is asuitable model to measure the success of the application of information systems in an organizationor company. This study will analyze factors that measure the success of DeLone & McLeaninformation systems model to the users of the Accurate accounting information systems in sixcompanies in the city of Sukabumi. The data collected from 37 respondents through surveys, is thenanalyzed using Partial Least Squares (PLS) available in SmartPLS 2.0 M3 software application.Results demonstrates that the quality of information and service quality does not have a significanteffect on the usage variable, while other variables have significant in measuring the success of theuse of Accurate accounting information systems to the value of R-squares for use 0.57, 0.94 for usersatisfaction and 0.94 for net benefit. And the value of goodness of fit (GoF) of 0.72 or 72%, so themodels are substantially enough to represent the research result.